2021
DOI: 10.1021/acsenergylett.1c01763
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Polymer Framework Modified SnO2 Enabling a Photostable α-FAPbI3 Perovskite Solar Cell with Efficiency Exceeding 23%

Abstract: Poly(ethylene glycol) diacrylate (PEGDA) is introduced into the SnO 2 dispersion as the polymer framework to hinder the agglomeration. The PEGDA-modified SnO 2 acted as the electron transport layer (ETL) in n-i-p structured perovskite solar cells (pero-SCs). It is demonstrated that the PEGDA plays multifunctional roles in the enhancement of photovoltaic performance and stability against illumination and humility. First, the PEGDA-modified SnO 2 ETL is more uniform, and its energy level matched well with the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 22 publications
6
112
0
Order By: Relevance
“…Beyond that, it can passivate the defects at the interface between perovskite and ETL and also result in better energy-level alignment between perovskite and ETL, which could facilitate the carrier transport and reduce the energy loss. [57] There are very few studies on polymers for modifying the buried bottom interface, but theoretical research has shown that these polymers have great potential to better regulate the bottom interface. Due to the inherent insulating properties of polymer materials, these make polymer materials a doubleedged sword.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond that, it can passivate the defects at the interface between perovskite and ETL and also result in better energy-level alignment between perovskite and ETL, which could facilitate the carrier transport and reduce the energy loss. [57] There are very few studies on polymers for modifying the buried bottom interface, but theoretical research has shown that these polymers have great potential to better regulate the bottom interface. Due to the inherent insulating properties of polymer materials, these make polymer materials a doubleedged sword.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Beyond that, it can passivate the defects at the interface between perovskite and ETL and also result in better energy‐level alignment between perovskite and ETL, which could facilitate the carrier transport and reduce the energy loss. [ 57 ]…”
Section: Organic‐based Interface Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported doping elements include Mg, [6] Nb, [7] Sb, [8] Ta, [9] Y, [10] Li, [11] Ga, [12] Mo, [13] rare-earth ion, [14] and alkali chloride. [15] The reported additives include triphenylphosphine oxide molecule, [16] carbon quantum dots, [17][18] carbon nanotubes, [19] graphene quantum dots, [20] LiF, [21] RbF, [22] EDTA-2M, [23] Nb 2 C MXenes, [24] gold nanostars, [25] black phosphorus, [26] polymer, [27] and so on. In addition, there are some report about multiple ETL with other metal oxides [28] and surface modification including π-conjugated small molecules, [29] thiophene, [30] p-amino benzenesulfonic acid, [31] 4-imidazoleacetic acid hydrochloride, [32] sulfonium salt, [33] TiCl 4 , [34] fullerene, [35][36] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve highly efficient PSCs using a SnO 2 ETL, SnO 2 ETL combination and surface modification techniques that can improve electron injection and suppress electron recombination have been developed [13]. Various inorganic metal oxides, such as ZnO [14], MgO [15], and TiO 2 [16,17], as well as organics, including carbon-based materials [18], self-assembled monolayers (SAM) [19], and polymers [20], have been adopted in SnO 2 ETL-based PSCs to combine with or modify SnO 2 . Among them, the conventional m-TiO 2 layer is the preferable candidate to be combined with the compact SnO 2 (c-SnO 2 ) layer because the mesoporous scaffold can facilitate sufficient pore filling of the light-absorbing layer and improve electron extraction and transport over a single c-SnO 2 layer [17,21].…”
Section: Introductionmentioning
confidence: 99%